Accessibility and usability of parks and playgrounds. Issue 2 (April 2018) - Perry, Meredith A.; Devan, Hemakumar; Fitzgerald, Harry; Han, Karen; Liu, Li-Ting; Rouse, Jack
Abstract: Background: Public parks and playgrounds are an environment for leisure activity, which all generations can enjoy at low or no financial cost. Evaluating the accessibility and usability of parks and playgrounds is crucial because their design, environment (natural and built) and safety could restrict participation of persons with disabilities. Objective: To evaluate the accessibility and usability of 21 public parks and playgrounds in three metropolitan cities of New Zealand. Secondary aims were to compare the accessibility and usability by park type (destination or neighborhood) and deprivation level (high and low). Methods: Twenty-one parks were evaluated. A stratified random sampling was used to select 18 parks (six from each city). Three additional parks were purposely selected (one from each city) at the request of each respective city council. The parks and playgrounds were evaluated using a customized tool. Data were analyzed using descriptive statistics. Results: None of the parks we evaluated met the national standards and/or international guidelines for park and playground design. We identified potential accessibility and usability issues with car parking spaces, path surfaces and play equipment as well as lack of lighting and fencing. The presence of amenities (e.g. toilets and drinking fountains) was more common in destination parks. Fewer parks in areas of higher deprivation had accessible car parking spaces and main paths wider than 1.5 m. Conclusion: Our evaluation identified potential design, environmental and safety barriers to park and playground based participation for persons with disabilities across the lifespan. A larger, more comprehensive evaluation of parks and playgrounds is required.